Effects of Vitamin D Deficiency on Incidence Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-analysis - Amraei, Mansour; Mohamadpour, Safoura; Sayehmiri, Kourosh; Mousavi, Seyedeh Fatemeh; Shirzadpour, Ehsan; Moayeri, Ardeshir (Frontiers in Endocrinology, 2018)
Introduction: Proper nutrition is important for overall health, and it reduces healthcare costs associated with malnutrition. Many studies have investigated vitamin D deficiency and its role in gestational diabetes and controversial data have reported. A comprehensive consideration of articles in this field provides the possibility of a general study of this relationship. This meta-analysis is an evaluation of the relationship between vitamin D deficiency and gestational diabetes. Material and methods: Different databases (such as PubMed, Science Information Institute (ISI), EmBase, Scopus, and the Cochrane Library) were searched for studies and eligible English articles published before February 2017 that have reported the risk of gestational diabetes in relation to vitamin D deficiency. This relationship was measured using odds ratios (ORs) with a confidence interval of 95% (CIs). The influence of each study was measured through sensitivity analysis. Funnel plots, Egger regression tests, and the Beg-Mazumdar correlation test were used to determine bias or publication bias. STATA (version 11.2) was used for all analyses. Results: Twenty-six studies were selected as eligible for this research and included in the final analysis. In general, vitamin D deficiency among mothers may be related to an increased risk of gestational diabetes (OR = 1.18; 95% confidence interval, 1.01-1.35; p<0.001). The serum level of 25(OH)D is less meaningful in people with gestational diabetes than in those who have normal glucose tolerance. Subgroup analysis showed that the results concerning this association may vary with study design, but do not change with country of origin. Conclusion: Some evidence has shown that vitamin D deficiency may increase the risk of gestational diabetes.